A distinct and replicable variant of the squamous cell carcinoma gene inositol polyphosphate‐5‐phosphatase modifies the susceptibility of arsenic‐associated skin lesions in Bangladesh. Issue 13 (10th March 2015) - Seow, Wei Jie; Pan, Wen‐Chi; Kile, Molly L.; Tong, Lin; Baccarelli, Andrea A.; Quamruzzaman, Quazi; Rahman, Mahmuder; Mostofa, Golam; Rakibuz‐Zaman, Muhammad; Kibriya, Muhammad; Ahsan, Habibul; Lin, Xihong; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Single‐nucleotide polymorphisms (SNPs) in inflammation, one‐carbon metabolism, and skin cancer genes might influence susceptibility to arsenic‐induced skin lesions. METHODS A case‐control study was conducted in Pabna, Bangladesh (2001‐2003), and the drinking‐water arsenic concentration was measured for each participant. A panel of 25 candidate SNPs was analyzed in 540 cases and 400 controls. Logistic regression was used to estimate the association between each SNP and the potential for gene‐environment interactions in the skin lesion risk, with adjustments for relevant covariates. Replication testing was conducted in an independent Bangladesh population with 488 cases and 2, 794 controls. RESULTS In the discovery population, genetic variants in the one‐carbon metabolism genes phosphatidylethanolamine N‐methyltransferase (rs2278952, P for interaction = .004; rs897453, P for interaction = .05) and dihydrofolate reductase (rs1650697, P for interaction = .02), the inflammation gene interleukin 10 (rs3024496, P for interaction = .04), and the skin cancer genes inositol polyphosphate‐5‐phosphatase (INPP5A; rs1133400, P for interaction = .03) and xeroderma pigmentosum complementation group C (rs2228000, P for interaction = .01) significantly modified the association between arsenic and skin lesions after adjustments for multiple comparisons. The significant gene‐environment interaction between a SNP in the INPP5A gene (rs1133400) and water arsenic with respect to the skin lesion risk was successfully replicated in an independent population (P for interaction = .03). CONCLUSIONS Minor allele carriers of the skin cancer gene INPP5A modified the odds of arsenic‐induced skin lesions in both main and replicative populations. Genetic variation in INPP5A appears to have a role in susceptibility to arsenic toxicity. Cancer 2015;121:2222–2229. © 2015 American Cancer Society.